The Effects of Intraoperative Electrical Stimulation on Regeneration and Recovery After Nerve Isograft Repair in a Rat Model. (May 2022) - Keane, Grace C.; Pan, Deng; Roh, Joseph; Larson, Ellen L.; Schellhardt, Lauren; Hunter, Daniel A.; Snyder-Warwick, Alison K.; Moore, Amy M.; Mackinnon, Susan E.; Wood, Matthew D.
Background: Therapeutic electrical stimulation (ES) applied to repaired nerve is a promising treatment option to improve regeneration. However, few studies address the impact of ES following nerve graft reconstruction. The purpose of this study was to determine if ES applied to a nerve repair using nerve isograft in a rodent model could improve nerve regeneration and functional recovery.Methods: Adult rats were randomized to 2 groups: "ES" and "Control." Rats received a tibial nerve transection that was repaired using a tibial nerve isograft (1.0 cm length), where ES was applied immediately after repair in the applicable group. Nerve was harvested 2 weeks postrepair for immunohistochemical analysis of axon growth and macrophage accumulation. Independently, rats were assessed using walking track and grid-walk analysis for up to 21 weeks.Results: At 2 weeks, more robust axon regeneration and greater macrophage accumulation was observed within the isografts for the ES compared to Control groups. Both walking track and grid-walk analysis revealed that return of functional recovery was accelerated by ES. The ES group demonstrated improved functional recovery over time, as well as improved recovery compared to the Control group at 21 weeks.Conclusions: ES improved early axon regeneration into a nerve isograft and was associated with increased macrophage and beneficial M2 macrophage accumulation within the isograft. ES ultimately improved functional recovery compared to isograft repair alone. This study supports the clinical potential of ES to improve the management of nerve injuries requiring a nerve graft repair.